Does Asset-Light Strategy Contribute to the Dynamic Efficiency of Global Airlines? - Wang, Wei-Kang; Lin, Fengyi; Irene, Wei Kiong Ting; Kweh, Qian Long; Lu, Wen-Min; Chiu, Tzu-Yu (Elsevier Ltd, 2017)
This study analyses the effect of asset-light strategy on the dynamic efficiency of global airlines from 2008 to 2013. First, a dynamic data envelopment analysis is employed to estimate the dynamic efficiency of global airlines. Second, the degree of asset-lightness is computed by combining the concepts of the DuPont equation and financial ratios. Third, a multivariate analysis is performed to analyze the association between asset-light strategy and dynamic efficiency. The findings show that asset-light strategy significantly enables global airlines to have better corporate performance. Overall, this study suggests that global airlines should efficiently manage and allocate their light resources to sustain challenges in the dynamic global airline industry.